Lithium metal negative electrode sheet, method of manufacturing the same, and battery
Patent Information
- Application Number
- CN202510779571.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-11
AI Technical Summary
[0004]有鉴于此,本发明致力于提供一种锂金属负极片及其制备方法和电池,以解决现有技术中锂金属电池产气膨胀的问题
[0019](1)本发明中所提供的锂金属负极片包括金属基底和以PCN-250的衍生材料为原料的涂层,PCN-250的衍生材料具有酯基偶氮苯基团。其中,金属有机骨架材料PCN-250的衍生材料具有稳定的孔道以及可调节的孔径大小,可以在不影响离子传输的情况下吸附副反应产生的副产物,防止锂金属电池在循环后期产生大量的副反应气体,进而解决因产气导致电芯鼓胀出现安全隐患。并且,PCN-250的衍生材料会在机械压力下发生结构转变,由于材料中偶氮苯基团的翻转,导致其结构由正方形变为菱形,而被压力影响后的PCN-250的衍生材料可以在电解液进入内部孔道后在孔道内部产生压力,将其结构将菱形变回正方形,具有良好的机械性能。此外,PCN-250的衍生材料的酯基偶氮苯基团中,酯基中的氧原子通过共价键与碳原子相连,使得酯基偶氮苯具有更好的化学稳定性。此外,在涂层中引入亲锂元素,可以在具有较大表面积的PCN-250的衍生材料中作为桥梁引导锂离子均匀沉积,增强锂金属电池的安全性能以及循环稳定性能。
Smart Images

Figure CN120637392B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a lithium metal anode sheet, its preparation method, and a battery. Background Technology
[0002] Lithium metal anodes have an extremely high theoretical capacity (3860 mAh g⁻¹), equivalent to 10 times that of commercial graphite anodes. -1 With its characteristics such as the lowest chemical potential (-3.04V relative to the standard hydrogen electrode), lithium metal anodes have long been considered the "holy grail" of all anode materials. However, before lithium metal anodes can be applied in practice, key scientific issues still need to be resolved: 1. Interfacial side reactions; 2. Lithium dendrites; 3. Volume effect; 4. Safety issues.
[0003] Because lithium metal batteries use pure lithium as the negative electrode, the impact of a safety accident is far greater than that of ordinary battery systems. During the lithium-ion deposition process, the non-uniform electric field distribution on the electrode surface leads to uneven lithium-ion flow distribution, causing uneven lithium deposition and ultimately forming lithium dendrites. These dendritic lithium dendrites can penetrate the separator, triggering a series of safety problems, such as thermal runaway and internal short circuits. Furthermore, lithium metal has high chemical and electrochemical reactivity, meaning it will react continuously with almost all liquid electrolytes at the interface. This results in the generation of a large amount of gas inside the battery, causing the cell to swell during cycling and creating a safety hazard. Summary of the Invention
[0004] In view of this, the present invention aims to provide a lithium metal anode sheet, its preparation method and battery, to solve the problem of gas expansion in lithium metal batteries in the prior art.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows:
[0006] The present invention provides a lithium metal anode sheet, the lithium metal anode sheet comprising a metal substrate and a coating disposed on at least one surface of the metal substrate along the thickness direction; the coating comprising a metal-organic framework material;
[0007] The metal-organic framework material includes a derivative of PCN-250, which has an ester-azophenyl group.
[0008] Optionally, the porosity of the metal-organic framework material is 50% to 70%, and the pore size of the metal-organic framework material is 0.6 to 1.5 nm.
[0009] Optionally, the coating further contains a lithium-loving metal element; optionally, the lithium-loving metal element includes at least one of zinc, tin, magnesium and aluminum; optionally, the atomic ratio of the lithium-loving metal element to the iron element in the PCN-250 derivative material is (0.01-0.03):(0.56-1.5).
[0010] Optionally, the coating further includes a binder and a conductive agent; optionally, the mass ratio of the metal-organic framework material, the binder, and the conductive agent in the coating is (0.7-0.9):(0.1-0.2):(0.05-0.1); optionally, the binder includes polyvinylidene fluoride; the conductive agent includes conductive carbon black.
[0011] Optionally, the thickness of the coating is 5 to 50 μm.
[0012] A second aspect of the present invention also provides a method for preparing a lithium metal anode sheet, comprising the following steps:
[0013] S1. PCN-250 material, carboxylic acid compound, volatile solvent containing hydroxyl group and water are mixed and subjected to pore-forming reaction and esterification reaction to obtain PCN-250 derivative material;
[0014] S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
[0015] Optionally, in step S1, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent, and water is (3-8):(2-6):(6-12):(10-20); Optionally, the carboxylic acid compound includes carboxylate and / or carboxylic acid; Optionally, the carboxylate includes acetate, preferably, the acetate includes at least one of zinc acetate, tin acetate, magnesium acetate, and aluminum acetate; Optionally, the carboxylic acid includes acetic acid; Optionally, the hydroxyl-containing volatile solvent includes at least one of methanol, ethanol, and propanol.
[0016] Optionally, in step S2, the method for preparing the slurry containing the PCN-250 derivative material includes stirring the PCN-250 derivative material, binder, conductive agent, and solvent; optionally, the solvent includes dimethylformamide and / or N-methyl-2-pyrrolidone.
[0017] Optionally, in step S1, the environmental conditions for the pore-forming reaction are a closed environment, the temperature of the pore-forming reaction is 80-95℃, and the time of the pore-forming reaction is 1-4h; Optionally, in step S1, the temperature of the esterification reaction is 110-140℃, and the time of the esterification reaction is 2-4h.
[0018] A third aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode comprises the aforementioned lithium metal negative electrode and / or a lithium metal negative electrode prepared according to the aforementioned preparation method. Through the above technical solution, the beneficial technical effects of the present invention are as follows:
[0019] (1) The lithium metal anode sheet provided in this invention includes a metal substrate and a coating made from a PCN-250 derivative material, which has an ester-based azophenyl group. The PCN-250 derivative material has stable channels and adjustable pore size, allowing it to adsorb byproducts generated by side reactions without affecting ion transport, preventing the generation of large amounts of side reaction gases in the later stages of lithium metal battery cycling, thus solving the safety hazard caused by cell swelling due to gas generation. Furthermore, the PCN-250 derivative material undergoes a structural transformation under mechanical pressure. Due to the inversion of the azophenyl groups in the material, its structure changes from square to rhombic. The PCN-250 derivative material, after being affected by pressure, can generate pressure inside the channels after the electrolyte enters, causing its structure to change back from rhombic to square, exhibiting good mechanical properties. In addition, in the ester-based azophenyl group of the PCN-250 derivative material, the oxygen atom in the ester group is covalently bonded to the carbon atom, giving the ester-based azophenyl group better chemical stability. Furthermore, introducing lithiophilic elements into the coating can act as a bridge to guide the uniform deposition of lithium ions in PCN-250 derivative materials with a large surface area, thereby enhancing the safety performance and cycle stability of lithium metal batteries.
[0020] (2) The method for preparing lithium metal anode sheets provided by the present invention uses common volatile solvents containing hydroxyl groups and water to carry out a pore-forming reaction with PCN-250 material, and adds carboxylic acid compounds. While the PCN-250 material is forming pores, the azophenyl groups therein will also react with the hydroxyl groups of the volatile solvent containing hydroxyl groups to generate hydroxyazobenzene. Furthermore, when the reaction is carried out at high temperature in a closed container, the volatile solvents containing hydroxyl groups and water will evaporate at a certain temperature. The evaporated gas cannot be discharged, and the gas will expand the pores that were originally of a certain diameter. The expanded pores will adsorb more gas. Finally, the generated hydroxyazophenyl groups will also react with the carboxyl groups of carboxylic acid compounds to generate ester groups (COOR'). The oxygen atoms in the ester groups are connected to the carbon atoms through covalent bonds, which makes the ester group azobenzene have better chemical stability.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0022] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0023] Figure 1 The diagram shows the structural formula of a derivative material of PCN-250. Detailed Implementation
[0024] This invention discloses a lithium metal anode sheet, its preparation method, and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0025] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0026] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0027] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0028] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0029] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0030] To address the problem of gas expansion in existing lithium metal batteries, the present invention employs the following technical solution:
[0031] The present invention provides a lithium metal anode sheet, the lithium metal anode sheet comprising a metal substrate and a coating disposed on at least one surface of the metal substrate along the thickness direction; the coating comprising a metal-organic framework material;
[0032] The metal-organic framework material includes a derivative of PCN-250, which has an ester-azophenyl group.
[0033] The lithium metal anode sheet of this invention comprises a metal substrate and a coating made from a PCN-250 derivative material, which has ester-based azophenyl groups. The PCN-250 derivative material, a metal-organic framework, possesses stable channels and adjustable pore sizes, allowing it to adsorb byproducts generated by side reactions without affecting ion transport. This prevents the generation of large amounts of side reaction gases in the later stages of lithium metal battery cycling, thus addressing the safety hazard of cell swelling caused by gas production. Furthermore, the PCN-250 derivative material undergoes a structural transformation under mechanical pressure. Due to the inversion of the azophenyl groups, its structure changes from square to rhombic. Under pressure, the PCN-250 derivative material can generate pressure within the channels after electrolyte enters, causing its structure to revert from rhombic to square, exhibiting excellent mechanical properties. In addition, in the ester-based azophenyl groups of the PCN-250 derivative material, the oxygen atom in the ester group is covalently bonded to the carbon atom, resulting in better chemical stability for the ester-based azophenyl group.
[0034] In this application, "PCN-250" refers to a metal-organic framework material with Fe as the metal and 3,3',5,5'-azobenzenetetracarboxylic acid as the ligand, with CAS number 1771755-22-6.
[0035] "PCN-250 derivative materials" mainly refer to materials based on PCN-250 that incorporate ester-based azophenyl groups. Specifically, the introduction method involves reacting the azophenyl groups and hydroxyl groups in the metal-organic framework material PCN-250 to generate hydroxyazobenzene, and then reacting the hydroxyazobenzene with carboxyl groups to generate ester-based azophenyl groups. The structural formula of the PCN-250 derivative materials is as follows: Figure 1 The chemical formula is shown in the figure, where R is hydrogen.
[0036] According to the present invention, the porosity of the metal-organic framework material can be 50% to 70%. In this invention, a suitable porosity of the metal-organic framework material helps to adsorb more gas, thus resolving the safety hazard caused by cell swelling due to gas production. As an example, the porosity of the metal-organic framework material can be any value from 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, and 70%, or any value within the range of any pair of values mentioned above. In this invention, if the porosity of the metal-organic framework material is too large, it will affect the transport of lithium ions; if the porosity of the metal-organic framework material is too small, it will result in limited gas adsorption.
[0037] According to the present invention, the pore size of the metal-organic framework material can be 0.6–1.5 nm. In this invention, a suitable pore size of the metal-organic framework material helps to adsorb the most harmful gases. As an example, the pore size of the metal-organic framework material can be any value from 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, and 1.5 nm, or any value within a range formed by any pair of the above values. In this invention, if the pore size of the metal-organic framework material is too large, it will affect the transport of lithium ions; if the pore size of the metal-organic framework material is too small, it will result in limited gas adsorption.
[0038] According to the present invention, the coating may also contain a lithium-loving metal element.
[0039] Optionally, the lithiophilic metal element includes at least one selected from zinc, tin, magnesium, and aluminum. In this invention, introducing a lithiophilic element into the coating can act as a bridge to guide the uniform deposition of lithium ions in the PCN-250 derivative material with a large surface area, thereby enhancing the safety performance and cycle stability of lithium metal batteries.
[0040] According to the present invention, the atomic ratio of the lithiophilic metal element to the iron element in the PCN-250 derivative material can be (0.01-0.03):(0.56-1.5). In the present invention, the atomic ratio of the lithiophilic metal element to the iron element in the PCN-250 derivative material facilitates uniform lithium-ion deposition without affecting lithium-ion transport. As an example, the atomic ratio of the lithiophilic metal element to the iron element in the PCN-250 derivative material can be any value among 0.01:0.56, 0.02:1, 0.03:1.5, 0.03:1, and 0.03:0.56, or any value within the range formed by any pair of the above values. In this invention, if the ratio of the number of lithium-ion metal elements to the number of iron elements in the PCN-250 derivative material is too large, it will result in too many atoms occupying the lithium-ion transport channels and affecting lithium-ion transport. If the ratio of the number of lithium-ion metal elements to the number of iron elements in the PCN-250 derivative material is too small, it will result in too few lithium-ion elements affecting the uniform deposition of lithium-ions, and too few iron elements affecting the formation of the PCN-250 derivative material, thereby affecting the amount of adsorbed gas.
[0041] According to the present invention, the coating may further include a binder and a conductive agent. That is, the coating includes a metal-organic framework material, a binder, and a conductive agent.
[0042] According to the present invention, the mass ratio of the metal-organic framework material, the binder, and the conductive agent in the coating can be (0.7–0.9):(0.1–0.2):(0.05–0.1). In this invention, a suitable mass ratio of the metal-organic framework material, binder, and conductive agent in the coating helps to form a uniform coating with low peel strength, which can be well composited with a metal substrate such as lithium strip. As an example, the mass ratio of the metal-organic framework material, binder, and conductive agent in the coating can be any value from 0.7:0.1:0.05, 0.8:0.2:0.07, 0.9:0.2:0.1, 0.9:0.1:0.07, and 0.9:0.1:0.05, or any value within the range of any pairwise values mentioned above.
[0043] Optionally, the adhesive comprises polyvinylidene fluoride.
[0044] Optionally, the conductive agent includes conductive carbon black.
[0045] According to the present invention, the coating may further include a crack-resistant agent. That is, the coating includes a metal-organic framework material, a binder, a conductive agent, and a crack-resistant agent.
[0046] According to the present invention, in the coating, the mass ratio of the metal-organic framework material, the binder, the conductive agent, and the crack inhibitor can be (0.7-0.9):(0.1-0.2):(0.05-0.1):(0.05:0.1). In the present invention, a suitable mass ratio of the metal-organic framework material, binder, conductive agent, and crack inhibitor in the coating helps to form a uniform coating with low peel strength, and the crack inhibitor can prevent the metal material from cracking or shedding powder when it is laminated with the substrate material. As an example, the mass ratio of the metal-organic framework, binder, conductive agent, and crack inhibitor in the coating can be any value among 0.7:0.1:0.05:0.05, 0.8:0.2:0.07:0.07, 0.9:0.2:0.1:0.1, 0.9:0.1:0.07:0.07, and 0.9:0.1:0.05:0.05, or any value within the range formed by any pair of the above values.
[0047] Optionally, the crack-resistant agent comprises silane compounds, preferably, the silane compounds comprise at least one of vinylsilane, aminosilane, and polysiloxane.
[0048] According to the present invention, the thickness of the coating can be 5–50 μm. In this invention, a suitable coating thickness allows for the adsorption of a large amount of gas without affecting lithium-ion transport. As an example, the coating thickness can be any value selected from 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, and 50 μm, or any value within a range formed by any pair of the above values. In this invention, if the coating thickness is too thick, it will lead to lithium-ion transport; if the coating thickness is too thin, it will result in limited gas adsorption.
[0049] Optionally, the metal substrate includes copper foil, nickel foil, lithium strip, or lithium alloy composite strip; preferably, the lithium alloy composite strip includes lithium-aluminum alloy composite strip, lithium-magnesium alloy composite strip, or lithium-tin alloy composite strip.
[0050] A second aspect of the present invention also provides a method for preparing a lithium metal anode sheet, comprising the following steps:
[0051] S1. PCN-250 material, carboxylic acid compound, volatile solvent containing hydroxyl group and water are mixed and subjected to pore-forming reaction and esterification reaction to obtain PCN-250 derivative material;
[0052] S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
[0053] The method for preparing lithium metal anode sheets provided by this invention uses common hydroxyl-containing volatile solvents and water to perform a pore-forming reaction with PCN-250 material, along with a carboxylic acid compound. During the pore-forming process of PCN-250 material, the azophenyl groups react with the hydroxyl groups of the hydroxyl-containing volatile solvent to generate hydroxyazobenzene. Furthermore, during the high-temperature reaction in a closed container, the hydroxyl-containing volatile solvent and water evaporate at a certain temperature. The evaporated gas cannot escape and expands the pores, which are originally of a certain diameter. The enlarged pores then adsorb more gas. However, if the pores become increasingly larger, the surface area of the PCN-250 material increases, which negatively impacts the lithium-ion transport capacity and weakens the battery's gas adsorption capacity. Finally, the generated hydroxyazophenyl groups also react with the carboxyl groups of the carboxylic acid compound to generate an ester group (COOR'). The oxygen atom in the ester group is covalently bonded to the carbon atom, giving the ester-based azobenzene better chemical stability.
[0054] According to the present invention, in step S1, the mass ratio of the PCN-250 material, the carboxylate, the hydroxyl-containing volatile solvent, and water can be (3-8):(2-6):(6-12):(10-20). In the present invention, a suitable mass ratio of PCN-250 material, carboxylate, hydroxyl-containing volatile solvent, and water helps to form an appropriate amount of PCN-250 derivative material. As an example, the mass ratio of PCN-250 material, carboxylate, hydroxyl-containing volatile solvent, and water can be any value from 3:2:6:10, 4:3:7:12, 5:4:9:14, 6:5:10:15, 7:6:12:20, and 8:6:12:20, or any value within the range of any pair of the above values.
[0055] Optionally, the carboxylic acid compounds include carboxylates and / or carboxylic acids.
[0056] Optionally, the carboxylate includes acetate, and preferably, the acetate includes at least one of zinc acetate, tin acetate, magnesium acetate, and aluminum acetate.
[0057] In this application, the metal in the acetate greatly improves the impact of the large surface area on lithium-ion transport and uniform deposition of the PCN-250' material.
[0058] Optionally, the carboxylic acid includes acetic acid.
[0059] Optionally, the hydroxyl-containing volatile solvent includes at least one of methanol, ethanol, and propanol.
[0060] According to the present invention, in step S1, the PCN-250 material can be obtained commercially or can be prepared by existing methods.
[0061] According to the present invention, in step S1, the method for preparing the PCN-250 material may include:
[0062] 3,3',5,5'-tetracarboxylated azobenzene, a metal source, and a solvent were mixed to obtain a mixed solution; the mixed solution was then mixed with an acid compound and subjected to a solvothermal reaction to obtain PCN-250 material.
[0063] Optionally, the mass ratio of the 3,3',5,5'-tetracarboxylated azobenzene to the metal source is 1:1;
[0064] Optionally, the metal source includes Fe3O(CH3COO)6;
[0065] Optionally, the solvent includes N,N-dimethylformamide;
[0066] Optionally, the ratio of the acid compound to the 3,3',5,5'-tetracarboxylated azobenzene is 10 mL: 3 g;
[0067] Optionally, the acidic compound includes glacial acetic acid;
[0068] Optionally, the temperature of the solvothermal reaction is 140°C, and the time of the solvothermal reaction is 12 hours.
[0069] Optionally, in step S2, the method for preparing the slurry containing the PCN-250 derivative material includes: stirring the PCN-250 derivative material, binder, conductive agent, and solvent; or, stirring the PCN-250 derivative material, binder, conductive agent, crack inhibitor, and solvent; optionally, the solvent includes dimethylformamide and / or N-methyl-2-pyrrolidone.
[0070] According to the present invention, in step S1, the environmental conditions for the pore-forming reaction can be a closed environment, the temperature of the pore-forming reaction can be 80–95°C, and the time of the pore-forming reaction can be 1–4 hours. As an example, the temperature of the pore-forming reaction can be any value from 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, and 95°C, or any value within the range formed by any pair of the above values; the time of the pore-forming reaction can be any value from 1 hour, 2 hours, 3 hours, and 4 hours, or any value within the range formed by any pair of the above values.
[0071] According to the present invention, in step S1, the temperature of the esterification reaction can be 110–140°C, and the time of the esterification reaction can be 2–4 hours. As an example, the temperature of the esterification reaction can be any value from 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, and 140°C, or any value within the range formed by any pair of the above values; the time of the esterification reaction can be any value from 2 hours, 2.5 hours, 3 hours, 3.5 hours, and 4 hours, or any value within the range formed by any pair of the above values.
[0072] According to the present invention, in step S1, after the esterification reaction is completed, a post-treatment may be included, which includes washing and drying the product obtained after the esterification reaction.
[0073] The washing reagent includes ethanol;
[0074] The drying temperature is 50–80°C, and the drying time is 10–20 hours. As an example, the drying temperature can be any value from 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, and 80°C, or any value within the range of any two of the above values. The drying time can be any value from 10 hours, 12 hours, 15 hours, 18 hours, and 20 hours, or any value within the range of any two of the above values.
[0075] According to the present invention, in step S2, the method of forming a coating on the base film with the slurry includes coating or transfer printing; the specific process of transfer printing includes: uniformly coating the slurry on the surface of the transfer base film to form a slurry layer, and obtaining the transfer base film after drying; and performing roll transfer printing between the transfer base film and a metal substrate, with the metal substrate and the slurry layer disposed opposite to each other to obtain the lithium metal anode.
[0076] A third aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode comprises the lithium metal negative electrode described above and / or a lithium metal negative electrode prepared according to the preparation method described above.
[0077] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0078] Example 1
[0079] The method for preparing a lithium metal anode sheet includes the following steps:
[0080] (1) 3g of 3,3',5,5'-tetracarboxylated azobenzene and 3g of Fe3O(CH3COO)6 were stirred and dispersed in 200mL of N,N-dimethylformamide for 1h to obtain a mixed solution; 10mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5h, and then placed in a vacuum drying oven for a solvothermal reaction at 140℃ for 12h. After the solvothermal reaction was completed, the product was naturally cooled to room temperature, filtered to obtain a precipitate, washed with ethanol and water alternately, and finally dried at 60℃ for 12h to obtain PCN-250 material;
[0081] (2) Mix 5g of PCN-250 material, 8mL of ethanol, 4g of zinc acetate and 15mL of water, and carry out a pore-forming reaction at 85°C for 2h in a sealed container. Then, raise the temperature to 120°C for esterification reaction for 3h. After the esterification reaction is completed, separate the product to obtain the lower layer solution. Wash the lower layer solution with ethanol and water, and finally dry it at 60°C for 12h to obtain the PCN-250 derivative material.
[0082] (3) Mix and grind 3g of PCN-250 derivative material, 0.85g of binder polyvinylidene fluoride, 0.22g of conductive agent conductive carbon black and 0.22g of crack inhibitor vinylsilane for 20min, then add N-methylpyrrolidone and grind for 30min to obtain slurry; coat the slurry onto PET base film and dry at 60℃ for 12h to obtain transfer base film; roll the transfer base film and lithium strip at 0.4MPS to obtain lithium metal negative electrode sheet.
[0083] Example 2
[0084] The method for preparing a lithium metal anode sheet includes the following steps:
[0085] (1) 3g of 3,3',5,5'-tetracarboxylated azobenzene and 3g of Fe3O(CH3COO)6 were stirred and dispersed in 200mL of N,N-dimethylformamide for 1h to obtain a mixed solution; 10mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5h, and then placed in a vacuum drying oven for a solvothermal reaction at 140℃ for 12h. After the solvothermal reaction was completed, the product was naturally cooled to room temperature, filtered to obtain a precipitate, washed with ethanol and water alternately, and finally dried at 60℃ for 12h to obtain PCN-250 material;
[0086] (2) Mix 5g of PCN-250 material, 8mL of ethanol, 8g of zinc acetate and 15mL of water, and carry out a pore-forming reaction at 85°C for 2h in a sealed container. Then, raise the temperature to 120°C for esterification reaction for 3h. After the esterification reaction is completed, separate the product to obtain the lower layer solution. Wash the lower layer solution with ethanol and water, and finally dry it at 60°C for 12h to obtain the PCN-250 derivative material.
[0087] (3) Mix and grind 3g of PCN-250 derivative material, 0.85g of binder polyvinylidene fluoride, 0.22g of conductive agent conductive carbon black and 0.22g of crack inhibitor vinylsilane for 20min, then add N-methylpyrrolidone and grind for 30min to obtain slurry; coat the slurry onto PET base film and dry at 60℃ for 12h to obtain transfer base film; roll the transfer base film and lithium strip at 0.4MPS to obtain lithium metal negative electrode sheet.
[0088] Example 3
[0089] The method for preparing a lithium metal anode sheet includes the following steps:
[0090] (1) 3g of 3,3',5,5'-tetracarboxylated azobenzene and 3g of Fe3O(CH3COO)6 were stirred and dispersed in 200mL of N,N-dimethylformamide for 1h to obtain a mixed solution; 10mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5h, and then placed in a vacuum drying oven for a solvothermal reaction at 140℃ for 12h. After the solvothermal reaction was completed, the product was naturally cooled to room temperature, filtered to obtain a precipitate, washed with ethanol and water alternately, and finally dried at 60℃ for 12h to obtain PCN-250 material;
[0091] (2) Mix 5g of PCN-250 material, 8mL of ethanol, 1g of zinc acetate and 15mL of water, and carry out a pore-forming reaction at 85°C for 2h in a sealed container. Then, raise the temperature to 120°C for esterification reaction for 3h. After the esterification reaction is completed, separate the product to obtain the lower layer solution. Wash the lower layer solution with ethanol and water, and finally dry it at 60°C for 12h to obtain the PCN-250 derivative material.
[0092] (3) Mix and grind 3g of PCN-250 derivative material, 0.85g of binder polyvinylidene fluoride, 0.22g of conductive agent conductive carbon black and 0.22g of crack inhibitor vinylsilane for 20min, then add N-methylpyrrolidone and grind for 30min to obtain slurry; coat the slurry onto PET base film and dry at 60℃ for 12h to obtain transfer base film; roll the transfer base film and lithium strip at 0.4MPS to obtain lithium metal negative electrode sheet.
[0093] Example 4
[0094] The method for preparing the lithium metal anode sheet differs from that in Example 1 in that:
[0095] The amount of ethanol used is 12 mL.
[0096] The rest are the same as in Example 1.
[0097] Comparative Example 1
[0098] The method for preparing a lithium metal anode sheet includes the following steps:
[0099] (1) 3g of 3,3',5,5'-tetracarboxylated azobenzene and 3g of Fe3O(CH3COO)6 were stirred and dispersed in 200mL of N,N-dimethylformamide for 1h to obtain a mixed solution; 10mL of glacial acetic acid was mixed with the mixed solution and stirred and dispersed for 0.5h, and then placed in a vacuum drying oven for a solvothermal reaction at 140℃ for 12h. After the solvothermal reaction was completed, the product was naturally cooled to room temperature, filtered to obtain a precipitate, washed with ethanol and water alternately, and finally dried at 60℃ for 12h to obtain PCN-250 material;
[0100] (2) Mix and grind 3g of PCN-250 material, 0.85g of binder polyvinylidene fluoride, 0.22g of conductive agent conductive carbon black and 0.22g of crack inhibitor vinylsilane for 20min, then add N-methylpyrrolidone and grind for 30min to obtain a slurry; coat the slurry onto a PET base film and dry at 60℃ for 12h to obtain a transfer base film; roll the transfer base film and lithium strip together at 0.4MPS to obtain a lithium metal negative electrode sheet.
[0101] Comparative Example 2
[0102] The method for preparing the lithium metal anode sheet differs from that in Example 1 in that:
[0103] The amount of ethanol used is 4 mL.
[0104] The rest are the same as in Example 1.
[0105] Battery fabrication and electrochemical performance testing
[0106] 1. Battery manufacturing
[0107] The negative electrode sheets prepared in the above embodiments and comparative examples were used to prepare lithium metal stacked batteries with Ni90.
[0108] 2. Electrochemical performance testing
[0109] (1) The volume of a fresh battery (initial volume) and the volume of a battery after cycling to 80% capacity retention rate (volume after cycling) were tested by the buoyancy method. The volume change rate was calculated as (initial volume - volume after cycling) / initial volume * 100%.
[0110] The specific test method for cycling to 80% battery capacity retention is as follows: The test temperature is 25℃. Connect the battery to the charging cabinet, first charge it to 4.35V with a constant current of 0.1C, let it stand for 5 minutes, then discharge it to 2.8V with a constant current of 0.1C, let it stand for 5 minutes. Repeat this step twice, then let it stand for 30 minutes to complete the formation step. Next, charge it to 4.35V with a constant current of 0.33C, then charge it to 4.35V with a constant voltage of 4.35V until the current ≤0.05C, let it stand for 5 minutes, then discharge it to 2.8V with a constant current of 0.5C, let it stand for 5 minutes. Repeat this step until the battery capacity retention reaches 80%. The test results are shown in Table 1 and... Figure 1 As shown.
[0111] Table 1
[0112] Example 1 45.6 57.2 25.5 Example 2 45.8 66.7 45.6 Example 3 46.2 68.5 48.3 Example 4 45.1 55.6 23.3 Comparative Example 1 44.9 72.8 62.1 Comparative Example 2 45.3 65.3 44.2
[0113] Table 1 shows that when the zinc acetate content is 4g, the ester functional groups in the PCN-250 derivative material formed by its reaction with PCN-250 contribute to the chemical stability of the material. During gas adsorption, the material does not undergo chemical changes, resulting in the lowest gas production volume after cycling. When the zinc acetate content is too high, the PCN-250 derivative material contains excess acetate ions in addition to the already formed ester functional groups, which affects the chemical stability of the material and thus its adsorption capacity, resulting in an increased gas production volume. Conversely, when the zinc acetate content is too low, the chemical stability of the PCN-250 derivative material containing ester functional groups is poor, further affecting its adsorption capacity and resulting in an increased gas production volume.
[0114] During the pore-forming reaction, ethanol, with a boiling point of 78.3℃, will vaporize when the reaction temperature exceeds this point. However, in a sealed container, the ethanol cannot evaporate, causing the PCN-250 material to expand from its original small or non-existent pores, thus increasing the pore size and enhancing its gas adsorption capacity. When the amount of ethanol decreases, the pores formed are neither large nor numerous enough, resulting in weak adsorption capacity. However, when the amount of ethanol increases, the number of pores increases, and their surface area also increases, which hinders the transport of lithium ions. Furthermore, when the pores increase to a certain extent, most of the electrolyte will enter the pores, causing the internal pressure of the PCN-250 material to be greater than the external pressure. This causes the structure of the PCN-250 material to deform from a square shape to a rhombus shape, reducing the mechanical properties of the PCN-250 material and consequently lowering the cycle performance of the battery.
[0115] Before the esterification reaction, after adding zinc acetate, the azophenyl group reacts with some of the hydroxyl groups in ethanol to form hydroxyazobenzene. During the esterification reaction, the hydroxyazobenzene reacts with the carboxyl groups in zinc acetate to generate a zinc-composite ester PCN-250 derivative material. The oxygen atom in the ester group is covalently bonded to the carbon atom, which makes the ester azobenzene more chemically stable. This ensures that even if the azophenyl group changes from a square to a rhombic shape under pressure, its chemical properties will not be affected. In addition, the introduced zinc ions also greatly improve the lithium-ion transport and uniform deposition of the PCN-250 derivative material due to its large surface area.
[0116] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A lithium metal anode sheet, characterized in that, The lithium metal anode sheet includes a metal substrate and a coating disposed on at least one surface of the metal substrate along the thickness direction; the coating includes a metal-organic framework material. The metal-organic framework material includes a derivative of PCN-250, wherein the derivative of PCN-250 has an ester-azophenyl group; The derivative material of PCN-250 is shown in formula (1): Equation (1) The porosity of the metal-organic framework material is 50%~70%; The pore size of the metal-organic framework material is 0.6~1.5 nm.
2. The lithium metal anode sheet according to claim 1, characterized in that, The coating also contains a lithium-loving metal element.
3. The lithium metal anode sheet according to claim 2, characterized in that, The lithiophilic metal element includes at least one of zinc, tin, magnesium, and aluminum.
4. The lithium metal anode sheet according to claim 2 or 3, characterized in that, The atomic ratio of the lithiophilic metal element to the iron element in the PCN-250 derivative material is (0.01-0.03):(0.56-1.5).
5. The lithium metal anode sheet according to claim 1, characterized in that, The coating also includes an adhesive and a conductive agent.
6. The lithium metal anode sheet according to claim 5, characterized in that, The mass ratio of the metal-organic framework material, the binder, and the conductive agent in the coating is (0.7~0.9):(0.1~0.2):(0.05~0.1).
7. The lithium metal anode sheet according to claim 5, characterized in that, The binder includes polyvinylidene fluoride; the conductive agent includes conductive carbon black.
8. The lithium metal anode sheet according to claim 1, characterized in that, The thickness of the coating is 5~50μm.
9. A method for preparing a lithium metal anode sheet according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. PCN-250 material, carboxylic acid compound, volatile solvent containing hydroxyl group and water are mixed and subjected to pore-forming reaction and esterification reaction to obtain PCN-250 derivative material; S2. Prepare a slurry containing the derivative material of PCN-250, and form a coating on the base film with the slurry.
10. The method for preparing a lithium metal anode sheet according to claim 9, characterized in that, In step S1, the mass ratio of the PCN-250 material, the carboxylic acid compound, the hydroxyl-containing volatile solvent, and water is (3~8):(2~6):(6~12):(10~20).
11. The method for preparing a lithium metal anode sheet according to claim 10, characterized in that, The carboxylic acid compounds include carboxylates and / or carboxylic acids.
12. The method for preparing a lithium metal anode sheet according to claim 11, characterized in that, The carboxylate includes acetate, which includes at least one of zinc acetate, tin acetate, magnesium acetate, and aluminum acetate.
13. The method for preparing a lithium metal anode sheet according to claim 11, characterized in that, The carboxylic acid includes acetic acid.
14. The method for preparing a lithium metal anode sheet according to claim 9, characterized in that, The hydroxyl-containing volatile solvent includes at least one of methanol, ethanol, and propanol.
15. The method for preparing a lithium metal anode sheet according to claim 9, characterized in that, In step S2, the method for preparing the slurry containing the PCN-250 derivative material includes stirring the PCN-250 derivative material, binder, conductive agent, and solvent.
16. The method for preparing a lithium metal anode sheet according to claim 15, characterized in that, The solvent includes dimethylformamide and / or N-methyl-2-pyrrolidone.
17. The method for preparing a lithium metal anode sheet according to claim 9, characterized in that, In step S1, the environmental conditions for the pore-forming reaction are a closed environment, the temperature of the pore-forming reaction is 80~95℃, and the reaction time is 1~4h; and / or, In step S1, the temperature of the esterification reaction is 110~140℃, and the time of the esterification reaction is 2~4h.
18. A battery, characterized in that, The battery includes a negative electrode, wherein the negative electrode includes a lithium metal negative electrode according to any one of claims 1 to 8 or a lithium metal negative electrode prepared by any one of claims 9 to 17.
Citation Information
Patent Citations
Electrode plate and lithium ion battery
CN113764643A
Composite diaphragm, preparation method thereof and solid-state lithium metal battery
CN117638402A